Epidemiology of immune thrombocytopenia in Yunnan Province and cytokine expression characteristics at different altitudes - Wen Yang; Jianfang Dong; Wei Zhang; Yaxian Tan; Fan Zhou; Jia Wang; Yanting Li; Li Ma; Hui Bi; Huabin Gao; Zeping Zhou (Hematology)
Background Primary immune thrombocytopenia (ITP) is an autoimmune hemorrhagic disorder characterized by low platelet counts. Currently, the epidemiology of ITP in China remains poorly understood.Methods A cross-sectional study was conducted to analyze data from newly diagnosed ITP patients in Yunnan Province from 2022 to 2023 to assess the epidemiological characteristics of ITP. Enzyme linked immunosorbent assay (ELISA) were conducted to detect plasma cytokine levels in ITP patients and healthy controls from two different altitude regions.Results This study reports for the first time an average incidence rate of 6.75 per 100,000 population for ITP in Yunnan Province, China. There was a significant difference in incidence rates between males and females, at 5.9 and 7.59, respectively. Infants under the age of 4 were identified as having the highest risk of ITP. After age 70, the incidence in males began to exceed that in females. This is different from previous reports in Japan, Europe and the United States. Additionally, there was no significant difference in the incidence of ITP based on altitude; however, mid-latitude regions had a higher concentration of ITP patients. Cytokine analysis was performed in 88 individuals, revealing significantly elevated Hypoxia-inducible factor alpha (HIF-1α) and Interleukin (IL-4) levels in ITP patients from high-altitude regions.Conclusion This study offers the first insights into the epidemiological characteristics of ITP in Yunnan Province and underscores the impact of altitude on cytokine variations in ITP patients. These findings offer valuable guidance for personalized treatment strategies and the formulation of public health policies for ITP.